191k views
5 votes
12

Solve using the Quadratic Formula for 2x2 + 5x – 3 = 0
x = -5, 7
b. X = -12,2
X = -3,42

User Nagual
by
4.8k points

2 Answers

9 votes

Explanation:


\tt{2 {x}^(2) + 5x - 3 = 0}


\sf{2 {x}^(2) + 5x + ( - 3) = 0}

Here , a = 2 , b = 5 & c = -3 {a is the coefficient of x² , b is the coefficient of x and c is the constant term }

Now ,


\tt{x = \frac{ - b± \sqrt{ {b}^(2) - 4ac } }{2a} }


\tt{x = \frac{ - 5± \sqrt{ {5}^(2) - 4 * 2 * ( - 3) } }{2 * 2} }


\sf{ x= ( - 5±7)/(4) }

Taking positive ( + ) sign :


\tt{x = ( - 5 + 7)/(4) = (1)/(2)}

Taking negative ( - ) sign :


\tt{x = ( - 5 - 7)/(4) = - 3}


\purple{ \boxed{ \boxed{ \tt{⤑ \: Our \: final \: answer : \boxed{ \underline{ \tt{x = (1)/(2) , \: - 3}}}}}}}

Hope I helped ! ツ

Have a wonderful day / night♡

▁▁▁▁▁▁▁▁▁▁▁▁▁▁▁▁▁▁▁▁▁▁▁▁▁▁▁▁

User Sukhmeet Sethi
by
4.9k points
5 votes
Step-by-step explanation
12 Solve using the Quadratic Formula for 2x2 + 5x – 3 = 0 x = -5, 7 b. X = -12,2 X-example-1
User Haley
by
4.4k points